A Parallel Thrombolysis Protocol with Nurse Practitioners As Coordinators Minimized Door-to-Needle Time for Acute Ischemic Stroke. (6th December 2011) - Sung, Sheng-Feng; Huang, Ying-Chieh; Ong, Cheung-Ter; Chen, Yu-Wei
Abstract : Introduction . Quick thrombolysis after stroke improved clinical outcomes. The study objective was to shorten door-to-needle time for thrombolysis. Methods . After identifying the sources of in-hospital delays, we developed a protocol with a parallel algorithm and recruited nurse practitioners into the acute stroke team. We applied the new protocol on stroke patients from October 2009 to September 2010. Patients from the previous two years were used for comparison. Results . For ischemic stroke patients within 3 hours of onset, the median time from arrival to computed tomography scanning was reduced from 29 to 20 minutes (P < 0.001 ) and the median time from arrival to neurology evaluation decreased from 61 to 43 minutes (P < 0.001 ). For those patients who received thrombolysis, the median door-to-needle time was shortened from 68.5 to 58 minutes (P < 0.05 ). Conclusions . The parallel thrombolysis protocol successfully improved the median door-to-needle time to below the guideline-recommended 60 minutes.